Recombination Between Endogenous and Exogenous Simian Virus 40 Genes. II. Biochemical Evidence for Genetic Exchange - Vogel, T. (1977)
The genome of the simian virus 40 (SV40) temperature-sensitive (ts) mutant tsD202 rescued by passage on transformed permissive monkey lines (see accompanying paper [Y. Gluzman et al., J. Virol. 24:534-540, 1977]) was analyzed by restriction endonuclease cleavage mapping to obtain biochemical evidence that the rescue of the ts phenotype results from recombination with the resident SV40 genome of the transformed cell. It was demonstrated that the endonuclease R· HaeIII cleavage site, which is located at 0.9 map unit in the standard viral genome (and which is in the proximity of the known map position of the tsD lesion), is missing in the DNAs of the parental tsD202 virus and of three independent revertants of tsD202. In contrast, this cleavage site was shown to be present in the DNAs of four out of five independently derived rescued D202 populations and in the DNA of the SV40 strain, 777, used to transform the monkey cells. Comparison of the endonuclease R· Hin(II + III) cleavage patterns of SV40 strain 777 DNA and tsD202 DNA revealed differences in the electrophoretic mobilities of Hin fragments A, B, and F. However, the corresponding Hin fragments from all four rescued D202 genomes were identical in their mobilities to those of tsD202 DNA, indicating that these regions of the rescued D202 genome are characteristic of the tsD202 parent. We conclude, therefore, that the genome of the rescued D202 virus is a true recombinant, since it contains restriction endonuclease cleavage sites characteristic of both parents, the endogenous resident SV40 genome of the transformed monkey cells and the exogenous tsD202 mutant.